ESTRATEGIAS COMUNICACIONALES Y SU INCIDENCIA EN LA INCLUSIÓN DE LOS ESTUDIANTES CON NECESIDADES EDUCATIVAS RELACIONADAS A LA DISCAPACIDAD EN LA U.T.B. EXTENSIÓN QUEVEDO. - Briones Picso, Pamela Maria (2022)
The present investigation is proposed with the objective of knowing how reading affects and how it contributes in the formative development of the students of the Social Communication career because nowadays it is not common to see students or natural persons sit and read a literary text, due to the fact that technology proposes a new style to solve our activities in a fast and instantaneous way, so that there is a lack of interest to implement in their lives the habit of reading, which provides us with knowledge and a great cognitive development. Reading today is replaced by new technologies and this is a problem for society by the simple fact of leaving aside something important like reading for something distracting that is technology, which brings us to our training process yes, but it will reach a point of falling into their networks and completely leave the importance of having a physical text in our hands. The fruit of this research is to make students and teachers understand how valuable it is to have the discipline of reading in our daily lives, so that they know the pros and cons of not leading a productive lifestyle and be agents of change and progress in a changing world. The same to encourage teachers to apply and implement teaching activities in academic training of students in the career of Communication at the Technical University of Babahoyo Extension Quevedo 2022.